Matjarr Djuyal: How Using Gesture in Teaching Gathang Helps Preschoolers Learn Nouns - Anjilkurri Radley; Caroline Jones; Jose Hanham; Mark Richards (Languages, 2021)
There are important efforts being made to revitalise Aboriginal languages in Australia, which are both pedagogically and culturally appropriate. This research seeks to expand the current knowledge of the effectiveness of gesturing as a teaching strategy for young children learning the Gathang language. An experimental method was used to investigate the effectiveness of gesture by employing a context in which other variables (e.g., other teaching pedagogies) could be held constant. Participants, age range 4–5.2 years, were taught Gathang nouns with gesture and without gesture, alongside verbal and pictorial instruction. After the teaching sessions, each child was assessed for their receptive and expressive knowledge of the Gathang nouns, at two time points, two days after instruction (post-test 1) and one week after (post-test 2). At post-test 2, children had stronger receptive knowledge for words they had learned with gesture than without. These findings contribute to a growing body of research attesting to the effectiveness of gesture for improving knowledge acquisition amongst learners. In the context of Aboriginal language revitalisation, gesture also aligns with traditional teaching practices and offers a relatively low-cost strategy for helping teachers assist their students in acquiring Aboriginal languages.